Decreasing influenza vaccine coverage among adults with high-risk chronic diseases in Spain from 2014 to 2017 - Maria A Martinez-Huedo; Ana Lopez-; Eduardo Mora-Zamorano; Valentin Hernández-Barrera; Isabel Jiménez-Trujillo; Jose J Zamorano-Leon; Rodrigo Jiménez-García (Taylor & Francis Group, 2020)
The objectives of this study were to estimate coverage of influenza vaccination in Spain among adults suffering chronic conditions, to assess time trends from 2014 to 2017 and to identify vaccine uptake predictors. We used individualized data of persons ≥15 y interviewed in the 2017 Spanish National Health Survey. Vaccine uptake and the presence of the chronic conditions analyzed (diabetes; cancer; chronic respiratory disease; chronic heart disease and cerebrovascular disease) were self-reported. Independent variables included sex, age and nationality. In 2017 overall influenza vaccination uptake among subjects with high-risk chronic conditions remained low (40.3%) and decreased significantly from 2014 (41.7%, adjusted OR 0.98 95%CI 0.84-0.98). The highest coverage was found among those with cerebrovascular disease (52.2%), diabetes (51.5%) and heart disease (51.4%) and the lowest figures for those suffering cancer (34.9%) and respiratory disease (35.1%). Coverage for cancer patients declined a 25% from 2014 to 2017. Older persons had higher coverages whereas females and immigrant population had lower uptakes. We conclude that influenza vaccination coverage among the high-risk population in Spain for suffering chronic conditions remains at a low level and has decreased significantly from 2014 to 2017, this affects more intensely to females and immigrants.